Acceptance and commitment group therapy (ACT-G) for health anxiety: a randomized controlled trial. Issue 1 (18th August 2015) - Eilenberg, T.; Fink, P.; Jensen, J. S.; Rief, W.; Frostholm, L.
Abstract : Background: Severe health anxiety is frequent and costly, yet rarely diagnosed or treated. Earlier treatment studies show problems with recruitment, dropout and recovery. In the current study, the authors aimed to test the effect of acceptance and commitment group therapy (ACT-G) compared to waitlist in patients with severe health anxiety. Method: During March 2010 to April 2012, 126 consecutively referred patients meeting research criteria for severe health anxiety were block-randomized (1:1) to ACT-G or a 10 months' waitlist (Clinicaltrials.gov, no. NCT01158430). Patients allocated to ACT-G were treated in seven groups of nine patients between December 2010 and October 2012 and received nine weekly 3-h group sessions and a booster session consisting of ACT techniques. The primary outcome was decided a priori as the mean change in self-reported illness worry on the Whiteley-7 Index (WI) from baseline to 10 months' follow-up. Secondary outcomes were improvement in emotional distress and health-related quality of life at 10 months' follow-up. Results: Intention-to-treat analysis showed a statistically significant mean difference of 20.5 points [95% confidence interval (CI) 11.7–29·4, p < 0.001] on the WI between the groups at 10 months, and the between-group effect sizes were large (Cohen's d = 0.89, 95% CI 0.50–1.29). The number needed to treat was 2.4 (95% CI 1.4–3.4, p < 0.001). Diagnosis and treatment were well accepted by the patients. Conclusions: ACT-G seems feasible, acceptable and effective in treating severe health anxiety.